2020
DOI: 10.1093/humrep/deaa094
|View full text |Cite
|
Sign up to set email alerts
|

Post-Caesarean section niche-related impaired fertility: hypothetical mechanisms

Abstract: ABSTRACT Caesarean section can result in an indentation of the myometrium at the site of the Caesarean scar, called a niche. Niches can cause symptoms of abnormal uterine blood loss, dysmenorrhoea, chronic pelvic pain and dyspareunia and are possibly related to subfertility. Various other explanations for the cause of subfertility after Caesarean section have been proposed in the literature, such as uterine pathology, intra-abdominal adhesions and women’s reprodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 68 publications
1
53
0
Order By: Relevance
“…The underlying mechanism that leads to adverse pregnancy outcomes among women with caesarean section after IVF may be attributed to the presence of a scar defect. A more recent review study by Vissers et al presented a series of hypotheses regarding the effect of a CSD on fertility outcomes [ 27 ]. The possible hypotheses relevant to this study are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism that leads to adverse pregnancy outcomes among women with caesarean section after IVF may be attributed to the presence of a scar defect. A more recent review study by Vissers et al presented a series of hypotheses regarding the effect of a CSD on fertility outcomes [ 27 ]. The possible hypotheses relevant to this study are as follows.…”
Section: Discussionmentioning
confidence: 99%
“…Caesarean scar niche has been suggested to underlie some cases of subfertility ( 13 , 22 ). In our current study we found that six women who had a subsequent pregnancy had caesarean scar niche (13%) and one woman who did not have a subsequent pregnancy had caesarean scar niche (14%) after initial treatment of caesarean scar pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…It is very important to emphasize that the relief of symptoms was declared by 93.3% of women after operative hysteroscopy vs. 44.4% of women after diagnostic hysteroscopy (p = 0.009). Moreover, the performed logistic regression analysis showed a significantly higher effectiveness of operative hysteroscopy compared to diagnostic hysteroscopy in the reduction of symptoms associated with spotting after sexual intercourse OR ratio (95% CI) 16.500 (2.301-344.405), p-value 0.017. The analysis of the effect of the hysteroscopic treatment and thus the improvement of the quality of life is presented in Table 4.…”
Section: Social Healthmentioning
confidence: 96%